Nori sheet imitation in form edible film With materials of protein myofibrillar tilapia - Bambang - Riyanto; Wini - Trilaksani; Lianny Eka Susyiana (Jurnal Pengolahan Hasil Perikanan Indonesia, 2014)
Nori is a traditional japanese food made from sea algae Phorphyra with a very large market demand. Phorphyra have ecophysiological aspects of the cultivation of the most successful, but only on the development of the East Asian subtropical climates. Edible film based polymer material of myofibrillar proteins is innovation can be developedto anticipate of those needs. Typical characteristics of nori and the availability of edible film, making the development of nori sheet imitation is possibly to be conducted.The purpose of the research was to developed formulations imitation nori sheet with the idea myofibrillar protein-based edible film of tilapia. Homogenisation myofibrillar proteins of tilapia concentration of 28% (w/v), 30% (w/v) and 32% (w/v) was performed with 3 ml of 1M NaOH (pH 11), 10% glycerol (plasticizer), and leaves suji solution, continued by casting, drying and hot smoking. Various concentrations were used and significantly gave effect to the thickness, hardness/fracturability or brittleness, content of protein, fat, ash, water, dietary fiber and potassium, but not for the tensile strength of the nori sheet imitation. Nori sheet imitation based on myofibrillar proteins of tilapia that characteristically almost equal with commercial nori is a concentration of 28% (w/v).Keywords: Edible film, myofibrillar protein, nori, tilapia